Ergebnisse und kritische Einschätzung einer Massenaufzucht von Perillus bioculatus (Fabr.) (Heteroptera: Pentatomidae). - Kahlow, Edith (Contributions to Entomology = Beiträge zur Entomologie, 1963)
There are discussed the problems of mass rearing of Perillus bioculatus (Fabr.), predaceous on all stages of the Colorado Beetle, based upon the results of investigations under laboratory conditions, the continuation of which is examined with special regard to acclimatization of the predator. There is stressed the possibility of a dislocation of mass rearing under field conditions with only one generation a year, a more natural adaption to climatic factors, a higher hibernating quote, and the resulting higher number of eggs during the main activity period of the Colorado Beetle in May and June.